Digital labor : the Internet as playground and factory - Scholz, Trebor (Routledge, 2013)
Digital Labor calls on the reader to examine the shifting sites of labor markets to the Internet through the lens of their political, technological, and historical making. Internet users currently create most of the content that makes up the web: they search, link, tweet, and post updates-leaving their ""deep"" data exposed. Meanwhile, governments listen in, and big corporations track, analyze, and predict users' interests and habits. This unique collection of essays provides a wide-ranging account of the dark side of the Internet. It claims that the divide between leisure time and work has vanished.